Farmers’ Knowledge and Perception of Apple Arthropod Pests in the Kigezi Highlands of Uganda - Kamusiime, Emilly; Natongo, Judith Ssali; Cosmas, Wacal; Tumuhaise, Venansio; Obua, Joseph (East African Nature and Science Organization, 2025)
This article examines the knowledge and perceptions of farmers on arthropod pests in Kigezi apple agroecology. Today, apple production in Kigezi persistently gives poor quality and low quantity apple fruits, and a significantly low percentage of Kigezi apples reach both local and international markets. This study’s data was collected from four districts of Kigezi which include; Kabale, Rukiga, Rubanda and Rukungiri where 25 apple growers were selected per district. Interviewing selected farmers was done from May to December, 2023, using structured and non-structured questionnaires. Collected data was analyzed using descriptive statistics where parametric and non-parametric tests were conducted and frequencies and percentages were generated from different responses. Results from analysis of variance (ANOVA) indicated a significant knowledge gap on pest species of Green apple aphids, Apple sawfly, Thrips and Apple rust mites across districts. Again, knowledge of all common pests of apple scales, coddling moth, apple maggot, apple bud weevil, rosy aphid, woolly apple aphid, common green capsid, apple grass aphid, green apple aphid, apple sawfly, thrips, apple rust mite and fruit tree spider red mite significantly differed among the farmers. It was noted that 37% of interviewed farmers were aware of apple arthropod pests. However, 82% of knowledgeable farmers were unable to identify nor classify these arthropod pests nor do they match any arthropod pest species to its associated damage symptoms. This led to 95% of respondents scoring less than 10% on knowledge of arthropod pests at both district and sub-county levels. This might have resulted from limited farmer training on arthropod pests and their associated damage symptoms. Therefore, for increased apple production in Kigezi, we recommend that farmers be equipped with knowledge of arthropod pests and their management. This could be achieved through comprehensive farmer sensitisation and training on arthropod pests.